Investigation of antimicrobial activity, bioassay-guided isolation and identification of antimicrobial compounds from swietenia macrophylla king - Mohammed Babiker, Suliman Blal (2016)
The plant genus Swietenia of which Swietenia macrophylla (Family: Meliaceae) belongs to, is a large mahogany tree growing in the rainforest of Malaysia and widely used in traditional medicine to treat various diseases. In this study, the physicochemical properties of the lipid, phytochemical and antimicrobial activity of extracts and fractions from Swietenia macrophylla were investigated. Then the compounds from the most active fraction were isolated and identified. The Minimum Inhibitory Concentrations (MIC) of these compounds were also identified. The dried plant parts (seeds, leaves, stems and roots) were subjected to maceration and later the most active crude extract (seeds extract) was fractionated into different classes according to the polarity with various solvents. The seed oil was extracted by solvent semi-continuous extraction method (Soxhlet) with hexane for six hours. The volatile compounds were identified in the extracts by GC-MS analysis, and the physicochemical properties of the seed oil were determined according to the standard methods. In the antimicrobial test, all the crude, fractions, seed oil and isolated compounds were investigated against nine microorganisms (all were lab strains) by using agar diffusion method. The microbes were: six bacteria, namely; Staphylococcus aureus, Bacillus subtilis, Enterococcus faecalis, Salmonella typhi, Pseudomonas aeruginosa, and Escherichia coli; and three funguses namely; Candida albicans, Aspergillus flavus and Aspergillus niger. The isolation and purification of active compounds has been carried out using chromatographic techniques (analytical HPLC and preparative-LC), and the structure elucidation of the isolated compounds based on spectroscopic techniques including, MS, IR and NMR. The GC-MS results showed three, five, eight, and ten compounds in the roots, stems, leaves, and seeds, respectively. The predominant compound existed in the all extracts was palmitic acid, with relative abundances of 2.03% (roots), 5.79% (seeds), 6.40% (stems), and 14.15% (leaves). The major compound in each part as: 1-tetradecene (18.08%); phytol (19.68%); linoleic acid (39.76%) and stearic acid (52.0%) for the stems, leaves, seeds and roots respectively. The physicochemical properties of the seeds oil were refractive index (1.46), specific gravity (0.954), viscosity (412.7), iodine value (71.5 mL/g), saponification value (211.75. mg KOH/g) and peroxide value (3.25%) are an attribute of the oil to be used for industrial purposes, such as in manufacturing of paint, varnish, and ink industries. The antimicrobial activity among the extracts was extremely broad against all tested organisms. Overall, among the crude extracts, the seeds extract showed more potent as antimicrobial activity than other parts against most tested microbes, whereas within fractionated seed fractions; fraction 3 (ethyl acetate fraction) is more potent. Compounds isolation and structural elucidation of the most bioactive fraction yielded four limonoids, namely swietenolide (1), proceranolide (2), 3-O-tigloyl-6-O-acetylswietenolide (3) and swietenine acetate (4). Among the isolated limonoids, swietenolide (1) showed highest activity against all of the tested organisms. The MIC values of the compounds ranged from 4 to 256 μg/mL. Conclusively, these results suggested that limonoids present in S. macrophylla were associated with antimicrobial activity. This provides the scientific evidence for the possible use of limonoids derived from S. macrophylla as a source of herbal antimicrobial agent(s).